2011
DOI: 10.3109/13816810.2011.610862
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial dysfunction in Pearson syndrome

Abstract: Mitochondrial disorders are associated with well recognized ocular manifestations. Pearson syndrome is an often fatal, multisystem, mitochondrial disorder that causes variable bone marrow, hepatic, renal and pancreatic exocrine dysfunction. Phenotypic progression of ocular disease in a 12-year-old male with Pearson syndrome is described. This case illustrates phenotypic drift from Pearson syndrome to Kearns-Sayre syndrome given the patient's longevity. Persistent corneal endothelial failure was noted in additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Consistent with this, in addition to having a high mitochondrial density, CE dysfunction is a common symptom associated with mitochondrial disorders, such as Pearson Syndrome, Kearns-Sayre syndrome and Leigh's syndrome (Boonstra et al, 2002, Chang et al, 1994, Hayashi et al, 2000, Kasbekar et al, 2013). However, despite the intense energetic demands imposed by the CE pump function, the metabolic mechanisms required for maintaining high levels of energy remain largely unexplored.…”
Section: Introductionmentioning
confidence: 57%
“…Consistent with this, in addition to having a high mitochondrial density, CE dysfunction is a common symptom associated with mitochondrial disorders, such as Pearson Syndrome, Kearns-Sayre syndrome and Leigh's syndrome (Boonstra et al, 2002, Chang et al, 1994, Hayashi et al, 2000, Kasbekar et al, 2013). However, despite the intense energetic demands imposed by the CE pump function, the metabolic mechanisms required for maintaining high levels of energy remain largely unexplored.…”
Section: Introductionmentioning
confidence: 57%
“…Guttae (as well as retinal dystrophy and optic neuropathy) do appear in other diseases linked to mitochondrial dysfunction such as Kearns-Sayer disease and Leber hereditary optic neuropathy. 30,31 Whether this is the secondary manifestation of mitochondrial dysfunction, well known to be a pathologic characteristic of methylmalonic acidemia, 32 is unknown, but is supported by a case study that described a late-onset cblC patient whose muscle biopsy results showed neurodegeneration and a mitochondrial respiratory chain defect with cytochrome oxidase (complex IV) deficiency. 33 Furthermore, a postmortem pathologic study of a 2-year-old cblC patient with macular degeneration 16 documented swollen mitochondria and large vacuoles in the corneal endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive onset of ocular symptoms mimicking Kearn-Sayre, including pigmentary retinopathy, external ophthalmoplegia, and corneal edema has been described. 2 However, ocular manifestations of the disease remain poorly characterized. We describe early-onset of corneal edema and pigmentary retinopathy in Pearson marrow-pancreas syndrome associated with severe photophobia.…”
Section: Discussionmentioning
confidence: 99%
“…1 This corneal edema is hypothesized to occur because the ion pumps in the endothelial cell layer fail. 2 The pumps depend on primary active transport to maintain fluid balance in the cornea, 3 and mitochondrial dysfunction depletes their energy source and leads to the corneal fluid imbalance observed in these diseases. Other possible explanations for the corneal edema include excess lactate accumulation in the cornea due to compensatory anaerobic glycolysis and increased apoptosis of endothelial cells due to mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation